“O CRISTO AFOGADO: UMA NÃO-CRISTOLOGIA” RELIGIÃO, LITERATURA E PÓS-COLONIALISMO - Beltran, Carlos José Beltrán (2015)
This dissertation seeks to deepen a crisis within theological liberation perspectives starting from postcolonial discourse. Liberation theology had promoted a profound revolution in third world theological studies since 1970. To continue this revolution we will read Gabriel Garcia Marquez “El ahogado más hermoso del mundo” (1968), analizing and assessing its cultural and political strategies. In order to accomplish this task we need to go beyond the secular/religious binary vision that divides the world into religious and non religious ideas/practices. We need a unified vision that comprehends the worldliness of those realities categorized as “religious” as well as those categorized as “non-religious”. Theology and Religious Studies, as the scientific discourse dealing with the economy of the exchange within world visions, practices and consciousness marked by a certain inherent mystery, have a fundamental roll in comprehending, evidencing, articulating and making available these cultural forces. The perception of existing symbols related to Jesus-Christ within this story gave us a path for the analyses, although we were not caught up within the disciplinary constraints implied in christological thinking. At the same time, there were no possibility of leaving untouched the imperial/colonial relation inherent to images and discourses on Jesus-Christ. We therefore build up a theoretical structure that could explicit the values, gestures and worldly horizons of GarcíaMárquez’s literary writing, being Christological or non Christological. We looked forward the destabilization of traditional frameworks of Theology and Religious Studies; destabilization of GarcíaMárquez writing as literature; and destabilization of the colonial/imperial geography which postulates the fictional realism of territories such us “Latin America”. We opened up a theoretical space that reads the story as a “non-christology”, displacing the disciplinary and classificatory imprisonment of the elements involved in the analysis. Critical works of Edward Said, Homi Bhabha and GayatrySpivak, as well as the critical works of Asian, African and Latin American feminist theologians shall enunciate the political emancipatory scenario that we will denominate theological secular criticism.